Role of Different Oral Anticoagulants Used During Diabetes-Related Complications in Patients with Atrial Fibrillation - Hassan Shabbir, Mansoor Ahmed Subhani, Shoaib Younis, Rabia Sehar, Hasnat Shabbir, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Globally, cardiovascular disease is the main contributor to mortality, accounting for about 17.5 million deaths, or 46.2% of deaths from non-communicable diseases. Objectives: The main objective of the study is to find the diabetes-related complications and mortality in patients with atrial fibrillation receiving different oral anticoagulants. Material and methods: This cross-sectional study was conducted in Pakistan Institute of Medical Sciences, hospital Islamabad from August 2021 to May 2022. The data were collected from 120 diabetic patients who were diagnosed with AF. After permission from the hospital ethical committee, a total of 120 patients meeting the inclusion and exclusion criteria was enrolled in the study. A detailed history of DM and physical examination were done to meet the inclusion and exclusion criteria. Results: The data were collected from 120 patients. Out of 120 participants, 60 were treated with warfarin while 60 were considered as the control group. The median age was 26 years in group I and 25.3 years in group II (p=0.705). Female cases counted for 41 (86%) and 19 (14%) in the I and II groups, respectively. Conclusion: It is concluded that patients with AF and diabetes have a high overall cardiovascular risk. Non–vitamin K antagonist oral anticoagulants were associated with lower hazards of diabetes complications and mortality than warfarin in patients with AF and DM.